2004
DOI: 10.1091/mbc.e03-05-0281
|View full text |Cite
|
Sign up to set email alerts
|

Novel Membrane Protein shrew-1 Targets to Cadherin-Mediated Junctions in Polarized Epithelial Cells

Abstract: While searching for potential candidate molecules relevant for the pathogenesis of endometriosis, we discovered a 2910-base pair cDNA encoding a novel putative 411-amino acid integral membrane protein that we called shrew-1. The putative open-reading frame was confirmed with antibodies against shrew-1 peptides that labeled a protein of ϳ48 kDa in extracts of shrew-1 mRNA-positive tissue and also detected ectopically expressed shrew-1. Expression of epitopetagged shrew-1 in epithelial cells and analysis by surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
78
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(84 citation statements)
references
References 40 publications
4
78
2
Order By: Relevance
“…15 SHREW1 encodes a novel transmembrane protein in adherens junctions. 16 The loss of adherens junctions has been shown to promote tumor cell infiltration and metastasis. 17,18 Thus, it is possible that The SHREW1 Gene, Frequently Deleted in Oligodendrogliomas, Functions to Inhibit Cell Adhesion and Migration …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 SHREW1 encodes a novel transmembrane protein in adherens junctions. 16 The loss of adherens junctions has been shown to promote tumor cell infiltration and metastasis. 17,18 Thus, it is possible that The SHREW1 Gene, Frequently Deleted in Oligodendrogliomas, Functions to Inhibit Cell Adhesion and Migration …”
Section: Resultsmentioning
confidence: 99%
“…16 To test whether SHREW1 has an anti-tumor effect, we transfected a SHREW1 (green fluorescent protein or GFP tagged) expression vector into a glioma cell line. A limiting factor in studies of oligodendroglioma is the paucity of oligodendroglioma cell lines and the lack of a well-characterized oligodendroglioma cell line that exhibits 1p allelic loss.…”
mentioning
confidence: 99%
“…The gene SHREW1 was expressed preferentially in fetal brain, total brain, spinal cord, cerebellum, and spleen. SHREW1 is predicted to encode a transmembrane-spanning protein and has recently been shown to interact specifically with E-cadherin/bcatenin complexes (Bharti et al, 2004), but little else is currently known regarding its function or that of its mouse homolog. A number of additional SRD genes for which some function could be determined are plausible as having tumor suppressor roles, including the putative transcription factors MGC33488, PHF13, KIAA0469, HES2, FLJ32096, LOC284509, and CAMTA1.…”
Section: Discussionmentioning
confidence: 99%
“…SHREW1 appears to be the single gene located in MDR2. Recently, the cDNA of SHREW1 was isolated from invasive endometriotic cells (Bharti et al, 2004). This gene encodes a B48kDa transmembrane protein, with its carboxy terminus being cytoplasmic, and does not belong to any protein family.…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic expression of SHREW1 in polarised epithelial cells showed that shrew1 protein colocalised with E-cadherin in adherens junctions, probably via binding of b-catenin. However, in nonpolarised invasive epithelial cells, shrew1 bound neither to N-cadherin and b-catenin (Bharti et al, 2004). E-cadherin is generally not expressed in brain tumours, except in benign meningiomas (Schwechheimer et al, 1998), whereas N-cadherin and b-catenin are detectable at cell -cell junctions in malignant astrocytic tumours (Utsuki et al, 2002).…”
Section: Discussionmentioning
confidence: 99%